Aspect of Reasoning Development on Authentic Assessment Indicators in Electronic School Book in Senior High School - Tarmini, Wini; Safi'i, Imam; Hikmat, Ade; Sobri (LPPM Undiksha, 2022)
Reasoning is one of the most fundamental aspects in solving problems. This study aims to analyses the development of reasoning in authentic assessment indicators contained in language electronic school books for high school. The method used in this research is content analysis. The subject of this study are electronic school books for Senior High School class X, XI, and XII, The research procedure carried out refers to the stages of qualitative research, namely data collection, data display, data reduction, and drawing or verifying. The data that has been collected is then analyzed by calculating the number or intensity of the reasoning aspects and the tendency of the spread of various aspects of reasoning which are grouped into five categories. The result of this study found that reasoning contained in Senior High School electronic school book has been developed quite well, but has not developed the aspect of reasoning proportionally. The reasoning aspect that is most often developed in authentic assessment indicators is identifying problems and identifying assumptions. Aspects of reasoning that have not been developed are related to formulating problems in the form of questions, choosing their own problems, give reasons for the solution, give reasons for the strategy used, and evaluate the systematic strategy. The results of this study can be used to measure the quality of developing authentic assessment indicator supplements contained in high school electronic school books.